Differential prognostic impact of complete blood count-related parameters by prior use of novel androgen receptor pathway inhibitors in docetaxel-treated castration-resistant prostate cancer patients. Issue 1 (January 2022) - Kobayashi, Hiroki; Shiota, Masaki; Sato, Nobuaki; Kobayashi, Satoshi; Matsumoto, Takashi; Monji, Keisuke; Kashiwagi, Eiji; Takeuchi, Ario; Inokuchi, Junichi; Shiga, Ken-ichiro; Yokomizo, Akira; Eto, Masatoshi
Abstract : There are multiple reports on the value of complete blood count (CBC)-related parameters on prognosis in docetaxel-treated castration-resistant prostate cancer (CRPC) patients before the emergence of androgen receptor pathway inhibitors (ARPIs). We investigated the prognostic significance of CBC-related parameters in docetaxel-treated CRPC patients. Patients treated with docetaxel chemotherapy for CRPC between 2008 and 2018 were included. We analyzed the relevance of CBC-related parameters to oncological prognosis in docetaxel chemotherapy, associated with prior use of novel ARPIs. Among 144 Japanese men treated with docetaxel, 49 men (34.0%) had already received ARPI therapy. A high neutrophil–lymphocyte ratio (NLR) was a prognostic factor for poor progression-free survival and overall survival (OS) in both univariate and multivariate analyses. In addition, a low hemoglobin (Hb) level and a high systemic immune-inflammation index (SII) were prognostic factors of poor OS in univariate analysis. Hb level was a prognostic factor of OS in both ARPI-naive and ARPI-treated patients. However, a high NLR and SII were only associated with a poor prognosis in ARPI-naive but not in ARPI-treated patients. Hb, NLR, and SII have been suggested to be prognosticators in docetaxel-treated CRPC patients. The differential prognostic value of NLR and SII between ARPI-naive and ARPI-treated patients may require caution when using these markers in docetaxel-treated CRPC patients. Abstract : Supplemental Digital Content is available in the text.